Cash Flow Hedging and Liquidity Choices - Disatnik, David; Duchin, Ran; Schmidt, Breno (Review of Finance, 2014)
Abstract This article studies the interaction between corporate hedging and liquidity policies. We present a theoretical model that shows how corporate hedging facilitates greater reliance on cost-effective, externally provided liquidity in lieu of internal resources. We test the model’s predictions by employing a new empirical approach that separates cash flow hedging from other hedging instruments. Using detailed, hand-collected data, we find that cash flow hedging reduces the firm’s precautionary demand for cash and allows it to rely more on bank lines of credit. Furthermore, we find a significant positive effect of cash flow hedging on firm value, where prior evidence is mixed.